Analysis of the Influence of Clearance on the Meshing Force and Friction Power Loss of Cycloid-pin Gear Transmission - Yutao Li; Shoufeng Jin; Hang Jiao; Yize Hou (Jixie chuandong)
Meshing clearance is one of the key factors affecting the transmission performance of cycloid-pin planetary drive such as load capacity，frictional power，vibration and noise. By using the principle of mesh between cycloidal gear and pins，the analysis model is well built for analyzing contact force and frictional power loss of cycloid gear and pin considering meshing clearance. By introducing comparisive coefficient，the influence of meshing clearance on contact force and frictional power of cycloid-pin pair is described. The analysis results show that the meshing clearance will significantly change the number of pins in the contact，thus changing the peak of contact force and frictional power loss，the increase of meshing clearance will lead to a significant rising of the peak contact force，but the frictional power loss will be slightly reduced. This method can provide a simple theoretical method for evaluating the influence of initial and worn clearance on contact characteristics of cycloid-pin pair.